Phytochemicals identification, anti-microbial, anti-oxidant and anti-diabetic activities of Polygala sphenoptera Fresen (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
Polygala sphenoptera Fresen, belonging to the family Polygalaceae, is a plant traditionally used in folk medicine for various health benefits. However, its chemical composition and pharmacological properties have not been explored. This study was to prepare and optimise the ethanolic extract of P. sphenoptera, investigate its phytochemical composition, and evaluate its anti-microbial, in-vitro anti-oxidant and anti-diabetic activities. The ethanolic extract of the authenticated whole plant of P. sphenoptera was investigated for the presence of phytochemicals and evaluated for anti-microbial properties by determining the minimum inhibitory concentration and zone of inhibition. The anti-oxidant capacity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging assay. The anti-diabetic potential was assessed by measuring α-amylase and α-glucosidase inhibitory activities. Phytochemical investigations indicate the presence of carbohydrates, flavonoids, tannins, alkaloids, and phenolic compounds. The phenolic content of the extract was found to be 8.733 mg GAE/g. The extract demonstrated significant anti-microbial activity against both bacterial and fungal strains. In-vitro studies indicated that the plant extract possesses strong anti-oxidant and anti-diabetic properties. Further detailed research will help to understand its mechanisms and validate its therapeutic potential.